The accessibility of English academic texts that were rewritten in plain language and according to document design principles: A Stellenbosch University case study - Gabriels, Carmen Allison Pamela (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.